63 Peripheral endothelial function in patients affected by pulmonary hypertension. Relationship between endothelial function, haemodynamic parameters, and therapy response. (8th December 2021) - Correale, Michele; Tricarico, Lucia; Croella, Francesca; Fortunato, Martino; Ceci, Vincenzo; Mazzeo, Pietro; Alfieri, Simona; Iacoviello, Massimo; Di Biase, Matteo; Brunetti, Natale D
Abstract: Aims: Pulmonary hypertension (PH) is defined as a mean pulmonary arterial pressure (mPAP) of 25 mmHg or greater at rest, confirmed by right heart catheterization (RHC). The World Health Organization has classified PH into five clinical subgroups. Pulmonary arterial hypertension (PAH) (group 1) is characterized by loss and obstructive remodelling of the pulmonary vascular bed. These patients are characterized haemodynamically by the presence of precapillary PH, defined as an mPAP of 25 mm Hg or greater, pulmonary artery wedge pressure (PAWP) of 15 mm Hg or less, and pulmonary vascular resistance (PVR) of three Wood units (WU) or greater. Pulmonary hypertension due to left-sided heart disease (LHD) (PH-LHD) (group 2) occurs in HF. Patients with PH-LHD usually have isolated postcapillary PH (PAWP >15 mm Hg and PVR <3 WU), although some of them have combined postcapillary and precapillary PH (PAWP >15 mm Hg and PVR ≥3 WU). PH due to chronic lung disease (CLD) (PH-CLD) and/or hypoxia (group 3) can occur in many lung diseases. These patients have precapillary PH. Chronic thromboembolic PH (CTEPH) (group 4) is characterized by obstruction of the pulmonary vasculature by organized thromboembolic material and vascular remodelling, resulting from prior pulmonary embolism. Patients with unclear and/or multifactorial mechanisms are listed as group 5. Specific pulmonary vasodilators are approved only in PAH patients. While research was predominantly focused on pulmonary vasculature, little is known about the peripheral endothelial damage in different vascular beds in PH patients. To evaluate the relationship between the peripheral endothelial function and the haemodynamic parameters, in order to provide a non-invasive method for the indirect evaluation of mean pulmonary pressure and vascular resistance, to predict if the PH is a precapillary or postcapillary, to select more accurately the patients who should undergo RHC. Moreover, we investigate if there is a possible correlation between endothelial dysfunction and response to specific PH therapies. Methods and results: Patients with suspected PH, based on symptoms, medical history, and clinics will undergo physical examination, ECG, echocardiography, and RHC. In all patients, endothelial function was assessed by FMD. Medical history, heart rate, systolic blood pressure, body mass index, WHO functional class, and medications were recorded. All patients underwent blood analysis, erythrocyte sedimentation rate (ERS), high sensitivity C-reactive protein (CRP), and NT-proBNP levels were assayed. Increased peripheral endothelial dysfunction in patients with precapillary PH, with a linear correlation between endothelium dysfunction and increased PVR at the right catheterization. To differentiate pre and post capillary PH forms by cut-off values of the FMD. The degree of endothelial dysfunction could be a marker of therapy response. Sequential combination therapy in the pre-capillary PH forms could be the one with a worst endothelial response than up-front combination therapy.